2003
DOI: 10.1103/physrevd.68.065006
|View full text |Cite
|
Sign up to set email alerts
|

Fermion zero modes inN=2supervortices

Abstract: We study the fermionic zero modes of BPS semilocal magnetic vortices in Nϭ2 supersymmetric QED with a Fayet-Iliopoulos term and two matter hypermultiplets of opposite charge. There is a one-parameter family of vortices with arbitrarily wide magnetic cores. Contrary to the situation in pure Nielsen-Olesen vortices, new zero modes are found which get their masses from Yukawa couplings to scalar fields that do not wind and are nonzero at the core. We clarify the relation between fermion mass and zero modes. The n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 23 publications
1
21
0
Order By: Relevance
“…F-term inflation, and therefore F-strings, can also be embedded in non-abelian theories or in N = 2 supersymmetric theories [11,12]. Although details change in that case, our main conclusions concerning the goldstino zero modes remain the same.…”
Section: F and D Strings In Global Susymentioning
confidence: 62%
“…F-term inflation, and therefore F-strings, can also be embedded in non-abelian theories or in N = 2 supersymmetric theories [11,12]. Although details change in that case, our main conclusions concerning the goldstino zero modes remain the same.…”
Section: F and D Strings In Global Susymentioning
confidence: 62%
“…From now on we will continue with both sets of BPS equations (for ǫ 1 and ǫ 2 ) of the full N=2 theory. For similar results on such an extra supersymmetry arising from an embedding of N = 1 into N = 2 in the context of global supersymmetry, see [40] and [41].…”
Section: Ansatz For the Bosonic Fields In N =mentioning
confidence: 77%
“…In [21] the large direct interaction between the two sectors of the theory was studied and it has been found that for large enough direct interaction, the global monopole will disappear from the system and leave behind a negative cosmological constant. The problem of stability of composite monopoles has been analyzed in [23] and [24].…”
Section: Introductionmentioning
confidence: 99%